Fikih Jual-Beli Pekerjaan - Saiful Bahri (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2014)
To understand the theory as in-debt named by fiqh. Basically, Islam just allows commodity trading like goods and services. Thus, this study will point out an Islamic perspective about employment or work trading.